Poverty and social exclusion in Macedonia, Serbia and Croatia: Status and policy responses - Gerovska Mitev, Maja (My University, 2015)
The paper discusses status and differences related to poverty, material deprivation and social exclusion based on statistical data from the Study on Income and Living Conditions (SILC) research in Macedonia, Serbia and Croatia. The countries covered in the paper are chosen due to their similar legacy of the social protection system, but also because they have different status with regard to the European Union (EU): a member state (Croatia), a candidate country with ongoing negotiations (Serbia) and a candidate country without negations (Macedonia). Apart from comparing and analyzing similarities and differences in the poverty rate, material deprivation and vulnerable groups in the three countries, the paper also analyzes countries' policy approaches in tackling poverty and social exclusion. In doing so, the correlation with the EU 2020 goals and targets is particularly emphasized. Comparative data from the SILC research shows that the scope of poverty and social exclusion is high in all three countries, however particular differences point to different dimensions of poverty which exist in these countries. While Croatia belongs to the EU countries in which income poverty is higher than the scope of material deprivation, Serbia and Macedonia have a reverse trend and belong to a smaller group of EU countries (Bulgaria, Romania, Latvia and Hungary) in which material deprivation is more pronounced than income poverty. Although policies aimed at tackling poverty and social exclusion refer to the EU 2020 targets, some of the shortcomings are still seen in all three countries : lack of revision of targets, lack of integrated approach between targets, as well as lack of profiling of vulnerable groups that are aimed to be lifted out of poverty. The paper stresses some of the shortcomings of the EU SILC data for poverty analysis in the three countries, and provides further recommendations for evidence based policy choices related to tackling poverty and social exclusion in Macedonia, Serbia and Croatia.